2000
DOI: 10.1074/jbc.m001333200
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Murine BiP/GRP78 with the DnaJ Homologue MTJ1

Abstract: The activity of Hsp70 proteins is regulated by accessory proteins, among which the most studied are the members of the DnaJ-like protein family. BiP/GRP78 chaperones the translocation and maturation of secreted and membrane proteins in the endoplasmic reticulum. No DnaJ-like partner has been described so far to regulate the function of mammalian BiP/GRP78. We show here that murine BiP/GRP78 interacts with the lumenal J domain of the murine transmembrane protein MTJ1 (J-MTJ1). J-MTJ1 stimulates the ATPase activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
70
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 85 publications
1
70
0
Order By: Relevance
“…Our immunoprecipitation studies ( Figure 5A) support this result in that the monoclonal antibody against Grp78 (anti-Grp78 M ) coprecipitated TF, whereas anti-Grp78 G did not. The N-terminal domain of Grp78 is known to mediate ATPase activity 25 and our studies imply that this function may be independent of TF regulation because we observed no effect with antibody against the N-terminal portion of Grp78 (data not shown). Future studies involving Grp78 mutants that are deficient in ATPase activity 26 may provide further direct evidence of the functional requirements of Grp78-mediated regulation of cell surface TF-mediated initiation of the coagulation protease cascades.…”
Section: Discussionmentioning
confidence: 42%
“…Our immunoprecipitation studies ( Figure 5A) support this result in that the monoclonal antibody against Grp78 (anti-Grp78 M ) coprecipitated TF, whereas anti-Grp78 G did not. The N-terminal domain of Grp78 is known to mediate ATPase activity 25 and our studies imply that this function may be independent of TF regulation because we observed no effect with antibody against the N-terminal portion of Grp78 (data not shown). Future studies involving Grp78 mutants that are deficient in ATPase activity 26 may provide further direct evidence of the functional requirements of Grp78-mediated regulation of cell surface TF-mediated initiation of the coagulation protease cascades.…”
Section: Discussionmentioning
confidence: 42%
“…The addition of the bulky AMP moiety can potentially hinder the contact between the domains and thereby disrupt the functional cycle of BiP. From an intermolecular perspective, AMPylation of BiP may also alter its interaction with binding partners such as DnaJ co-chaperone (53)(54)(55) or nucleotide exchange factors (56 -58).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated experimentally that Scj1 and another J-protein, Jem1, act to chaperone unfolded proteins in the yeast ER (5,15). In contrast, yeast Sec63 (16), its putative mammalian orthologue hSec63 (17), and mammalian MTJ1 (18,19), all of which are transmembrane J-proteins, seem to be directly involved in protein translocation across the ER membrane. Their similarity to bacterial DnaJ is restricted to the J-domain.…”
mentioning
confidence: 99%